2015
DOI: 10.1111/rssa.12102
|View full text |Cite
|
Sign up to set email alerts
|

Selection Error in Single- and Mixed Mode Surveys of the Dutch General Population

Abstract: Summary This study compares the extent of selection error (non‐response and coverage error) evoked by the four major contemporary modes of data collection (face to face, telephone, mail and Web) and three sequential mixed mode designs (telephone, mail and Web with face‐to‐face follow‐up) for the case of the Dutch Crime Victimization Survey. Sociodemographic characteristics and target variables from the survey serve as benchmark variables. A special two‐wave experimental design allows studying design difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
(46 reference statements)
2
25
0
1
Order By: Relevance
“…However, few studies have attempted to estimate the magnitude of selection errors before and after switching modes, while controlling for measurement differences. One recent study using a combination of data from population registers, a single mode benchmark, and a re-interview design (Klausch et al 2015a) observed an increase in response rates as a result of mixing modes sequentially (a face-to-face follow-up of web, mail and CATI surveys), but found no consistent reduction in selection errors present in estimates from the starting modes. Selection error was, however, reduced for some estimates from the mixed mode surveys as a result of bringing it closer in line with the selection error of the single mode (face-to-face) benchmark (ibid.…”
Section: Estimating the Effect Of Mixing Modes On Survey Errors And Amentioning
confidence: 99%
See 4 more Smart Citations
“…However, few studies have attempted to estimate the magnitude of selection errors before and after switching modes, while controlling for measurement differences. One recent study using a combination of data from population registers, a single mode benchmark, and a re-interview design (Klausch et al 2015a) observed an increase in response rates as a result of mixing modes sequentially (a face-to-face follow-up of web, mail and CATI surveys), but found no consistent reduction in selection errors present in estimates from the starting modes. Selection error was, however, reduced for some estimates from the mixed mode surveys as a result of bringing it closer in line with the selection error of the single mode (face-to-face) benchmark (ibid.…”
Section: Estimating the Effect Of Mixing Modes On Survey Errors And Amentioning
confidence: 99%
“…As a result, the available evidence as to the effects of mixing modes on different error sources, as well as on the TSE, remains somewhat inconclusive. In relation to selection errors, for example, several studies have analysed response rates and sample composition as proxies, and have confirmed that both can improve in mixed mode designs compared to single mode designs, depending on which modes are combined and how (e.g., Dillman et al 2014;Eva et al 2010;Fowler et al 2002;Greene et al 2008;Link and Mokdad 2006;Millar and Dillman 2011;Lynn 2013;Klausch et al 2015a). However, few studies have attempted to estimate the magnitude of selection errors before and after switching modes, while controlling for measurement differences.…”
Section: Estimating the Effect Of Mixing Modes On Survey Errors And Amentioning
confidence: 99%
See 3 more Smart Citations